Alcohol - Connolly, Sean (North Mankato, MN : Smart Apple Media, 2006)
A book about the risks and what consuming Alcohol can do to a person.
Alcohol and you -- Alcohol basics -- Just what happens? -- After-effects -- Trapped by alcohol -- Peer pressure -- Mixed messages -- Deadly dangers -- Setting limits -- School rules -- Spotting problems.
Keywords: Alcoholism; Children -- Alcohol use; Alcoholism -- Prevention